Increased mental stress among undergraduate medical students in south-western Saudi Arabia during the COVID-19 pandemic - Awadalla, Nabil J.; Alsabaani, Abdullah A.; Alsaleem, Mohammed A.; Alsaleem, Safar A.; Alshaikh, Ayoub A.; Al-Fifi, Suliman H.; Mahfouz, Ahmed A. (PeerJ, 2022)
Background The COVID-19 pandemic has disrupted the daily life and academic trajectory of many students. The objectives of this study were to evaluate the effect of the pandemic on perceived stress levels among medical students. Methods Comparative pre-pandemic and pandemic surveys were conducted among samples of undergraduate medical students. Students responded to a questionnaire including personal and academic data, and Cohen’s Perceived Stress Scale (PSS). Results Overall, the prevalence of high perceived stress during the pandemic (20.6%) was significantly higher (p = 0.001) than pre-pandemic (11.6%). A multivariable analysis revealed that the independent factors associated with high perceived stress were: participation in the study during the pandemic (aOR = 1.79, 95% CI: 1.22–2.63), female sex (aOR = 1.74, 95% CI: 1.23–2.47), younger age (aOR = 1.62, 95% CI: 1.04–2.55) and lower family income (aOR = 1.50, 95% CI: 1.12–2.03). PSS score was negatively correlated with increasing age, family income, and academic level. PSS score was positively correlated with: worries about the possible disruption of education or exams, excessive news exposure, worries about the possibility of COVID-19 infection, and the effects of mandatory isolation and social distancing. Conclusion The COVID-19 pandemic increased the level of stress among medical students. Female students, younger students, and those in lower academic grades are the most at risk of having high stress. Worries about possible academic disruptions due to the pandemic are significant stressors. The implementation of online stress management programs is recommended.
Keywords: COVID-19 pandemic; Medical students; Perceived stress; Stressors